Tomografia de ruído sísmico de ambiente na Província Borborema com estações de período curto - Silva, Cícero Costa da (2020)
Analysis of ambient seismic noise has proved to be a viable alternative to earthquake-generated seismic wave analysis. Although for a long time it was commonly discarded from earthquake recordings, it has been shown that the cross correlation of ambient seismic noise allows the recovery of the Green’s function between receivers. Moreover, seismic noise has the property of propagating uninterruptedly and independently of the occurrence of earthquakes, allowing for high resolution tomographic studies in low seismicity regions. Over the past two decades, the correlation of seismic noise between pairs of seismographic stations has been widely utilized in surface-wave tomography studies. In particular, for the northeast Brazil region, tomography studies used temporary and permanent broadband stations to investigate the deep structure (upper crust) of the Borborema Province; however, in addition to the broadband stations mentioned above, there is a large volume of data collected by 22 short-period stations that could improve the resolution of these tomographic studies. Thus, the goal of this MSc dissertation is to investigate whether short-period data: (i) can be used in surface-wave tomography studies, and (ii) can be combined with broadband data in a single tomographic inversion. Through the cross correlation of the recorded ambient seismic noise between short-period stations and subsequent stacking, the emergence of the dispersive, fundamental-mode Rayleigh waves was verified. It was also found that the dispersion curves (group and phase) could be satisfactorily obtained for periods of up to 10 s (after removal of the instrumental response), using standard surface-wave analysis techniques, and that it was indeed feasible to invert them together with dispersion curves from broadband recordings. The results obtained in the Borborema Province show that, for the 5 to 10 s period range, it was possible to define structures such as the Sergipe-Alagoas basin and the Borborema Plateau, which were not well delineated in previous tomographic studies.